Agriculture value chain finance in Viet Nam - de Brauw, Alan; Herskowitz, Sylvan; Ambler, Kate; Hoa, Nguyen Le; Trang, Truong Thi Thu; Thuy, Nguyen Thi; Anh, Bui Tuan; Trung, Nguyen Chi; Moyes, Tom; Middleton, Mark; Toth, Russell (Australian Centre for International Agricultural Research, 2020)
This report describes the present state of agricultural value chain finance in Viet Nam and suggests policies that could help expand its availability. We first consider the features of a policy environment needed for agricultural value chain finance to flourish.